Solid oxide fuel cell cathode and manufacturing process thereof
By using the cathode doped rare earth oxide intermediate layer and discretely distributed cathode point structure in the cathode of solid oxide fuel cell, the thermal mechanical instability problem of perovskite cathode materials is solved, and high thermal matching between the cathode and the electrolyte layer is achieved Improved properties and electrochemical properties.
Patent Information
- Application Number
- CN202411213812.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-31
- Publication Date
- 2024-12-13
AI Technical Summary
Thermomechanical instability of perovskite cathode materials leads to weak thermomechanical compatibility with other battery modules, and there are problems such as reduced redox reaction activity and limited adjustment effect of thermal expansion.
Doped rare earth oxides are used as the cathode intermediate layer material, and a discretely distributed cathode point structure is designed in the cathode body. The thermal stress differences caused by temperature changes are buffered through the appropriate thermal expansion characteristics of the cathode intermediate layer itself, combining the multi-layer sub-intermediate layer and The gradient density design of the cathode point layer improves the thermal matching between the cathode and the electrolyte layer.
The interface peeling or cracks caused by thermal expansion are significantly reduced, the thermal matching and electrochemical properties of the cathode layer and the electrolyte layer are improved, and the long-term stability and durability of the battery are enhanced.
Smart Images

Figure CN119133470A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of solid oxide fuel cells, and in particular to a solid oxide fuel cell cathode and a manufacturing process thereof. Background Art
[0002] The cathode is a key component of the solid oxide fuel cell (SOFC). Its core function is to capture hydrogen ions (i.e. protons) from the anode and, under the catalytic action of the catalyst, cause these hydrogen ions to combine with oxygen molecules to generate water molecules and release electrons. These released electrons are then directed to the external circuit to form an electric current, providing the required electrical energy for the device.
[0003] In the cathode design process, it is crucial to pursue high efficiency, stable and long-lasting performance. Currently, the widely used cathode materials include perovskite structured oxides, such as LaMnO 3 These materials are favored for their excellent electronic and ionic conductivity, as well as high catalytic activity for oxygen splitting and reduction processes. However, relying solely on the inherent properties of the material is not enough to meet performance requirements. Therefore, it is necessary to further optimize its performance by adjusting the structure and micromorphology of the cathode. For example, by designing a reasonable pore structure, an effective channel can be provided for the diffusion of oxygen molecules, and the contact area between the cathode and the electrolyte layer can be increased, thereby improving the reaction efficiency.
[0004] In addition, the chemical compatibility between the cathode and the electrolyte layer is also an important factor that must be considered in the design. To ensure the long-term stable operation of SOFC, the cathode material must maintain good chemical compatibility with the electrolyte layer material to avoid harmful chemical reactions or phase changes during long-term operation.
[0005] In Chinese patent CN202310953536.4, a series of methods for reducing the thermal expansion coefficient of cobalt-based electrodes are proposed, including incorporating transition metal elements into the lattice, compounding perovskite electrode materials with electrolyte layers, introducing A-site defects in perovskites, and the formation of in-situ thermal expansion inhibition phases. The goal of these technologies is to reduce the thermal expansion coefficient of cobalt-based electrodes to a level that matches a specific electrolyte layer, thereby alleviating thermomechanical instability. However, these methods also have certain limitations, such as the possibility of adversely affecting the redox reaction activity of the cathode and weakening the electrochemical performance of the battery; at the same time, these methods can only reduce the thermal expansion coefficient to a certain limit, and the adjustment effect is limited for significant thermal expansion differences; in addition, these methods also involve complex material modification or synthesis processes, which are not conducive to large-scale production and cost control. Summary of the invention
[0006] The main purpose of the present invention is to provide a solid oxide fuel cell cathode and its manufacturing process, aiming to solve the problem of thermomechanical instability of perovskite cathode materials resulting in weak thermomechanical compatibility of cathode materials with other battery components.
[0007] In order to achieve the above object, the present invention provides a solid oxide fuel cell cathode, comprising:
[0008] The cathode middle layer is made of rare earth oxide doped material;
[0009] The cathode body comprises a plurality of cathode points discretely distributed and combined on the cathode intermediate layer, wherein the cathode points comprise a plurality of cathode point layers combined in the thickness direction, wherein the cathode body is made of a perovskite type material.
[0010] Furthermore, the density of the plurality of cathode point layers on the cathode point increases by 5% to 20% in a direction away from the cathode middle layer.
[0011] Furthermore, the cathode intermediate layer includes a plurality of sub-intermediate layers connected in a thickness direction.
[0012] Furthermore, the cathode intermediate layer includes at least three sub-intermediate layers; the density of the sub-intermediate layers at the outer layer in the thickness direction increases gradually from 5% to 20% toward the density of the sub-intermediate layers at the middle part in the thickness direction.
[0013] Furthermore, the material of the cathode body is Co-based perovskite.
[0014] Furthermore, the material of the cathode body is La x Ag (1-x) CoO 3 .
[0015] Furthermore, the material of the cathode intermediate layer is gadolinium-doped ceria.
[0016] The present invention also provides a manufacturing process, the steps comprising:
[0017] S1. Complete cathode intermediate layer slurry configuration;
[0018] S2, taking cathode intermediate layer slurry to complete the lamination printing of sub-intermediate layers to form a substrate, wherein each sub-intermediate layer is dried after printing, and the sub-intermediate layers together constitute an intermediate layer;
[0019] S3, completing cathode body slurry configuration;
[0020] S4, taking the cathode body slurry and using a porous film layer to print the stacked layers of sub-cathode dots on the substrate to form a cathode prefabricated sheet, wherein each batch of sub-cathode dots is dried after printing, and the sub-cathode dots at the same position together constitute an independent cathode dot;
[0021] S5. Complete sintering of the cathode prefabricated sheet.
[0022] Furthermore, the step of S3 includes:
[0023] Disposing a plurality of cathode point layer slurries with concentration gradient differences;
[0024] The steps of S4 include:
[0025] Take multiple cathode dot layer slurries and use a porous membrane layer to print the stacked sub-cathode dot layers on a substrate to form a cathode prefabricated sheet, wherein each batch of sub-cathode dot layers are dried after printing, and the sub-cathode dot layers at the same position together constitute an independent cathode point, and the density of multiple cathode dot layers on the cathode point increases by 5% to 20% in the direction away from the cathode middle layer.
[0026] Furthermore, the step S1 includes:
[0027] S1, configuring a plurality of sub-intermediate layer slurries with different concentrations to form a gradient;
[0028] The steps of S2 include:
[0029] Take multiple sub-intermediate layer slurries to complete the stacking printing of sub-intermediate layers to form a base sheet, wherein each sub-intermediate layer is dried after printing, and the sub-intermediate layers together constitute an intermediate layer, and the density of the sub-intermediate layer in the outer layer in the thickness direction increases gradually from 5% to 20% toward the density of the sub-intermediate layer in the middle in the thickness direction.
[0030] The solid oxide fuel cell cathode and its manufacturing process provided by the present invention can buffer the thermal stress difference between the cathode body and the electrolyte layer when the temperature changes through the suitable thermal expansion characteristics of the cathode intermediate layer itself, and prevent interface peeling or cracking caused by thermal expansion mismatch. The cathode body includes discretely distributed cathode points. During the thermal cycle, since the cathode body has a very small surface area, the total amount of deformation caused by thermal expansion is also greatly reduced, so that the cathode layer will not deform violently at the electrolyte layer interface. Compared with the traditional electrode-electrolyte layer interface, the interface layer cracking caused by thermal stress deformation can be greatly reduced, and the thermal matching of the cathode layer and the electrolyte layer is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Electrochemical performance test (IV and IP curves) of the solid oxide fuel cell cathode of the first embodiment of the present invention after being made into a full cell, (a) the test condition is 30 ml / min; (b) the test condition is 50 ml / min;
[0032] Figure 2The DRT diagram of the solid oxide fuel cell cathode of the first embodiment of the present invention under the full-scale sampling data strategy after being made into a full cell: (a) test temperature 750 degrees Celsius, hydrogen flow rate 30, 50 ml per minute; (b) test temperature 850 degrees Celsius, hydrogen flow rate 30, 50 ml per minute;
[0033] Figure 3 A representative electrochemical impedance Nyquist plot of the solid oxide fuel cell cathode of the first embodiment of the present invention is evaluated during the thermal cycle of the electrode after being made into a full cell;
[0034] Figure 4 The first embodiment of the present invention is a solid oxide fuel cell cathode polarization resistance test after being made into a full cell, and the polarization resistance response of 50 thermal cycles between 700-400°C (heating rate is 30 degrees Celsius per minute, passive cooling rate is about 7.5 degrees Celsius per minute, and the total cumulative test time is 90 hours);
[0035] Figure 5 The electrochemical impedance Nyquist diagrams of a single cell under open circuit conditions after the solid oxide fuel cell cathode of the present invention is made into a full cell (Example 1 and Example 2): (a) Example 1, test temperature 700-850 degrees Celsius; (b) Example 2, test temperature 700-850 degrees Celsius.
[0036] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0037] It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention.
[0038] Those skilled in the art will appreciate that, unless expressly stated otherwise, the singular forms "a", "an", "said", "above", and "the" used herein may also include plural forms. It should be further understood that the term "comprising" used in the specification of the present invention refers to the presence of the features, integers, steps, operations, elements, units, modules, and / or components, but does not exclude the presence or addition of one or more other features, integers, steps, operations, elements, units, modules, components, and / or groups thereof. It should be understood that when we refer to an element as being "connected" or "coupled" to another element, it may be directly connected or coupled to the other element, or there may be intermediate elements. In addition, the "connection" or "coupling" used herein may include wireless connection or wireless coupling. The term "and / or" used herein includes all or any unit and all combinations of one or more associated listed items.
[0039] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.
[0040] In one embodiment of the present invention, a solid oxide fuel cell cathode includes:
[0041] The cathode middle layer is made of rare earth oxide doped material;
[0042] The cathode body comprises a plurality of cathode points discretely distributed and combined on the cathode intermediate layer, wherein the cathode points comprise a plurality of cathode point layers combined in the thickness direction, wherein the cathode body is made of a perovskite type material.
[0043] In the present invention, a solid oxide fuel cell cathode is provided. In a complete solid oxide fuel cell, an anode and an electrolyte are arranged corresponding to the cathode. A typical anode material is nickel oxide / yttrium stabilized zirconia, which combines the characteristics of nickel oxide and yttrium stabilized zirconia and exhibits excellent electrochemical and mechanical properties. Electrolyte materials include stabilized zirconia, doped cerium oxide, bismuth oxide, etc. Among them, yttrium stabilized zirconia has been widely studied and applied due to its good chemical stability and moderate oxygen ion conductivity. With the deepening of research, new materials and improved electrolyte designs are constantly being developed to further improve the performance of SOFC and reduce costs. In the process of forming the entire battery, the material selection of the electrolyte layer is preferably yttrium stabilized zirconia, which provides an efficient conduction channel for oxygen ions between the cathode and the anode.
[0044] The cathode interlayer is a key part of the cathode structure and is located between the cathode body and the electrolyte. The main function of the cathode interlayer is to provide good electron and ion conduction to promote the occurrence of electrochemical reactions. At the same time, it also needs to have good thermal stability and chemical stability to adapt to the high temperature environment of solid oxide fuel cells. Common cathode interlayer materials include doped oxides, such as doped rare earth oxides (such as doped cerium oxide, doped lanthanum oxide, etc.). When the temperature changes, the appropriate thermal expansion characteristics of the cathode interlayer itself buffer the thermal stress difference between the cathode body and the electrolyte layer to prevent interface peeling or cracks caused by thermal expansion mismatch.
[0045] The cathode of a solid oxide fuel cell is a key component of the battery. It is responsible for the oxidation reaction that occurs when the battery is running, usually an oxygen reduction reaction. There are many options for cathode materials. Material selection is crucial to the performance of solid oxide fuel cells. It affects the operating temperature, current density, durability, and cost of the battery. The main cathode material options include perovskite materials, copper-based composite materials, chromate materials, and metal-ceramic composite materials. Among them, the perovskite structure is a common crystal structure with ABO 3 Type of chemical formula. This type of material has been widely studied and applied due to its good electrical conductivity and chemical stability. For example, perovskite materials based on lanthanum, strontium and cobalt are common cathode materials. The cathode body includes discretely distributed cathode points. The thickness of the cathode body is designed and adjusted according to actual needs, generally around 30 microns. During the thermal cycle, due to the small surface area of the cathode body, the total amount of deformation caused by thermal expansion is also greatly reduced, so that the cathode layer will not deform violently at the electrolyte layer interface. The discretely distributed cathode points reduce the sharp increase in the total displacement of adjacent atoms caused by the temperature rise, and reduce the risk of electrode thermal cycle stratification failure. Compared with the traditional electrode-electrolyte layer interface, the interface layer cracking caused by thermal stress deformation can be greatly reduced, and the thermal matching of the cathode layer and the electrolyte layer is greatly improved. The spacing between each cathode point on the plane can be about 1 mm, and the specific adjustment design is based on the actual situation.
[0046] The process selection during the sintering process is crucial, and it is necessary to take into account the porosity formation of the cathode body, the close adhesion with the electrolyte layer, and the suppression of thermal expansion delamination failure to achieve good thermal matching and electrochemical performance.
[0047] In a typical implementation, a gadolinium-doped cerium dioxide slurry is printed on the electrolyte and then dried. The cathode powder (La 0.95 Ag 0.05 CoO 3 ) is configured as cathode body slurry, and a dispersed spot coating process is used to evenly and layer-coat the cathode body slurry on the intermediate layer. After the sintering process is completed, the full battery is completed. Under different test temperatures and hydrogen flow rates, the full battery exhibits high power density and good thermal cycle stability. For example, at 700 degrees Celsius, in a 100-hour polarization resistance test, the polarization impedance fluctuation amplitude was only 0.4% during 31 to 50 cycles, indicating that the cathode has excellent long-term durability and stability. Refer to the subsequent method embodiments for the specific implementation process, which will not be repeated here.
[0048] In summary, the appropriate thermal expansion characteristics of the cathode intermediate layer itself can buffer the thermal stress difference between the cathode body and the electrolyte layer when the temperature changes, preventing interface peeling or cracking caused by thermal expansion mismatch. The cathode body includes discretely distributed cathode points. During the thermal cycle, due to the small surface area of the cathode body, the total amount of deformation caused by thermal expansion is greatly reduced, so that the cathode layer will not deform violently at the electrolyte layer interface. Compared with the traditional electrode-electrolyte layer interface, the interface layer cracking caused by thermal stress deformation can be greatly reduced, and the thermal matching of the cathode layer and the electrolyte layer is greatly improved.
[0049] In one embodiment, the density of the plurality of cathode point layers on the cathode point increases by 5% to 20% in a direction away from the cathode middle layer.
[0050] In this embodiment, considering the considerations of dispersion and combination, the densities of multiple cathode dot layers are differentiated and gradient, so that the density of the cathode dot layer closest to the cathode middle layer is the smallest, and the degree of mutual combination between the cathode middle layer and the cathode dot layer is improved, and a better combination effect can be formed with the cathode middle layer. The density of the cathode dot layer in the outer layer is relatively increased to provide superior electrical and chemical properties. The density increase trend value of the specific cathode dot layer is adapted and adjusted according to the number of cathode dot layers.
[0051] In one embodiment, the cathode intermediate layer includes a plurality of sub-intermediate layers coupled in a thickness direction.
[0052] In this embodiment, considering that the cathode intermediate layer with a large thickness is similar to the cathode body, it is also unfavorable for the drying or sintering process. Thermal stress deformation during battery operation may cause structural failure of the cathode intermediate layer itself. The cathode intermediate layer is arranged as a plurality of sub-intermediate layers combined in the thickness direction. During the processing, the sub-intermediate layers are sequentially printed and dried, so that the structural stability of the entire cathode intermediate layer is high. During the drying process of the sub-intermediate layers, the degree of drying is preferably limited, and thorough drying is also unfavorable for the printing process.
[0053] In one embodiment, the cathode intermediate layer includes at least three sub-intermediate layers; the density of the sub-intermediate layers at the outer layer in the thickness direction increases gradually from 5% to 20% toward the density of the sub-intermediate layers at the middle layer in the thickness direction.
[0054] In this embodiment, the density of the sub-middle layer is also differentiated with reference to the density increment setting of the cathode point layer. Since the two sides of the cathode middle layer in the thickness direction need to form a bond with the electrolyte and the cathode body respectively, the density of the sub-middle layer in the outer layer in the thickness direction is reduced, and the density of a certain layer of the sub-middle layer in the middle of the thickness direction is the largest. Specifically, the density difference of the sub-middle layer is adjusted according to the number of sub-middle layers. The density differentiation of the sub-middle layer can improve the bonding performance of the cathode middle layer with the electrolyte and the cathode body, and the bonding performance between the sub-middle layers itself is also improved.
[0055] In one embodiment, the material of the cathode body is Co-based perovskite.
[0056] In this embodiment, the Co-based perovskite material has the characteristics of excellent oxygen reduction activity and excellent conductivity. The test results in the subsequent related embodiments also show that La 0.95 Ag 0.05 CoO 3 As a cathode, the test results are superior in all aspects. In fact, Co-based perovskites need to face a more serious problem of excessive thermal expansion coefficient.
[0057] In one embodiment, the cathode body is made of La x Ag (1-x) CoO 3 .
[0058] In this embodiment, the value range of x is between 0.90 and 0.97, and is preferably 0.95.
[0059] In one embodiment, the material of the cathode intermediate layer is gadolinium-doped ceria.
[0060] In this embodiment, GDC (Gadolinium-doped Ceria) is used as the cathode intermediate layer, and its main function is to provide thermal expansion buffer and reduce the thermal mechanical stress between the cathode body and the electrolyte layer. The GDC material has a moderate thermal expansion coefficient, which can effectively relieve the thermal stress between the cathode body and the electrolyte layer, and has good ionic conductivity, which is conducive to charge transfer.
[0061] The present invention also provides a manufacturing process, the steps comprising:
[0062] S1. Complete cathode intermediate layer slurry configuration;
[0063] S2, taking cathode intermediate layer slurry to complete the lamination printing of sub-intermediate layers to form a substrate, wherein each sub-intermediate layer is dried after printing, and the sub-intermediate layers together constitute an intermediate layer;
[0064] S3, completing cathode body slurry configuration;
[0065] S4, taking the cathode body slurry and using a porous film layer to print the stacked layers of sub-cathode dots on the substrate to form a cathode prefabricated sheet, wherein each batch of sub-cathode dots is dried after printing, and the sub-cathode dots at the same position together constitute an independent cathode dot;
[0066] S5. Complete sintering of the cathode prefabricated sheet.
[0067] In this embodiment, in steps S1 and S2, the cathode intermediate layer is printed and dried. In a laboratory production process, a screen printing method is used to uniformly deposit the cathode intermediate layer slurry on the upper surface of the electrolyte layer through a stainless steel screen and dry it at a temperature of 100 degrees Celsius. Then a layer of cathode intermediate layer slurry is applied. This process should be repeated three times to make the cathode intermediate layer have sufficient thickness. Specifically in the industrial production process, the process is adjusted according to the actual equipment conditions.
[0068] In steps S3 and S4, the cathode body is printed and dried. In a laboratory printing process, micropores of about 0.02 square centimeters are poked on the masking film, and 3×3 are closely arranged (in other embodiments, other types of arrays can also be arranged). Multiple coatings: After the first coating is dried, subsequent coating and drying are carried out to complete the half-cell. (Ensure that the coating thickness is about 35 microns) Before subsequent coating, it is also necessary to gently roll over the dried paint surface to remove dust.
[0069] In step S5, the half-cell is placed in a box-type resistance furnace and heated at a rate of 2 degrees Celsius per minute to reach a sintering temperature (600 degrees Celsius). Maintain this temperature for 1 hour to prepare a full cell, form a strong electrode-electrolyte layer interface, and ensure the overall electrochemical performance and thermal stability of the battery.
[0070] In one embodiment, the step of S3 includes:
[0071] Disposing a plurality of cathode point layer slurries with concentration gradient differences;
[0072] The steps of S4 include:
[0073] Take multiple cathode dot layer slurries and use a porous membrane layer to print the stacked sub-cathode dot layers on a substrate to form a cathode prefabricated sheet, wherein each batch of sub-cathode dot layers are dried after printing, and the sub-cathode dot layers at the same position together constitute an independent cathode point, and the density of multiple cathode dot layers on the cathode point increases by 5% to 20% in the direction away from the cathode middle layer.
[0074] In this embodiment, under different concentrations of the cathode dot layer slurry, the density of the cathode dot layer after drying is different. The density of the cathode dot layer closest to the cathode middle layer is the smallest, and the degree of mutual bonding between the cathode middle layer and the cathode dot layer is improved, so that a better bonding effect can be formed with the cathode middle layer. The density of the cathode dot layer in the outer layer is relatively improved to provide superior electrical and chemical properties.
[0075] In one embodiment, the step S1 includes:
[0076] Disposing a plurality of sub-middle layer slurries with different concentrations to form gradients;
[0077] The steps of S2 include:
[0078] Take multiple sub-intermediate layer slurries to complete the stacking printing of sub-intermediate layers to form a base sheet, wherein each sub-intermediate layer is dried after printing, and the sub-intermediate layers together constitute an intermediate layer, and the density of the sub-intermediate layer in the outer layer in the thickness direction increases gradually from 5% to 20% toward the density of the sub-intermediate layer in the middle in the thickness direction.
[0079] In this embodiment, since the cathode intermediate layer needs to be bonded to the electrolyte and the cathode body on both sides in the thickness direction, the density of the sub-intermediate layer in the outer layer in the thickness direction is reduced, and the density of a sub-intermediate layer in the middle of the thickness direction is the highest. The density differentiation of the sub-intermediate layers can improve the bonding performance of the cathode intermediate layer with the electrolyte and the cathode body, and the bonding performance between the sub-intermediate layers themselves is also improved.
[0080] In summary, the solid oxide fuel cell cathode and its manufacturing process provided by the present invention, through the appropriate thermal expansion characteristics of the cathode intermediate layer itself, buffers the thermal stress difference between the cathode body and the electrolyte layer when the temperature changes, and prevents interface peeling or cracking caused by thermal expansion mismatch. The cathode body includes discretely distributed cathode points. During the thermal cycle, since the cathode body has a very small surface area, the total amount of deformation caused by thermal expansion is also greatly reduced, so that the cathode layer will not deform violently at the electrolyte layer interface. Compared with the traditional electrode-electrolyte layer interface, the interface layer cracking caused by thermal stress deformation can be greatly reduced, and the thermal matching of the cathode layer and the electrolyte layer is greatly improved.
[0081] Embodiment 1:
[0082] La was prepared by sol-gel method. 0.95 Ag 0.05 CoO 3The cathode material is uniformly coated on the GDC interlayer using a dispersed dot coating process and then sintered to the YSZ electrolyte. The cathode interlayer is printed and dried using a screen printing method, and the distance between the lower surface of the screen and the upper surface of the fixed substrate is adjusted with a screw micrometer in the range of 1-1.5 mm. Subsequently, the cathode interlayer slurry is evenly distributed on the screen. A handheld rubber scraper is evenly reciprocated to scrape the screen at a speed of 2 cm per second. This ensures stable deposition of the cathode interlayer slurry on the substrate (such as a combination of electrolyte and anode). The angle between the rubber scraper and the screen is 60-75 degrees, and the cathode interlayer slurry is evenly deposited on the upper surface of the electrolyte layer through the stainless steel screen, and the printing process is thus enhanced. This layer is then placed on an iron plate and dried at a temperature of 100 degrees Celsius. Then another layer of cathode interlayer slurry is applied, and this process should be repeated three times to give the cathode interlayer a sufficient thickness.
[0083] Printing and drying of cathode body. In a laboratory printing process, a foam roller is selected for rolling. A needle-shaped tool is used to poke micropores of about 0.02 square centimeters on the masking film, and 3×3 are arranged closely. In the process of making cathode body slurry, an appropriate amount of PVP and pine alcohol mixed binder (6wt.%) is added to the cathode powder raw material to adjust the viscosity suitable for rolling. Before rolling, it is necessary to ensure that the coating surface is clean, flat, free of dust, grease and other impurities. During the rolling process, the 3×3 micropores are placed in the center of the substrate, and one-third of the roller is immersed in the paint. The roller is gently squeezed to help the paint absorb evenly, remove excess paint and evenly distribute the paint on the roller. From top to bottom or from left to right, maintain a certain speed and force to ensure that the paint is evenly distributed. Multiple-pass coating: After the first coat of coating is dry, subsequent coating and drying are carried out to complete the half-cell. (Ensure that the thickness of the coating is about 35 microns) Before subsequent coating, it is also necessary to gently roll over the dried paint surface to remove dust.
[0084] In step S5, the half-cell is placed in a box-type resistance furnace and heated at a rate of 2 degrees Celsius per minute to reach different sintering temperatures (300, 600 and 900 degrees Celsius), kept warm for 1 hour, and a full cell is prepared at the same time (including a group of four full cells that are only dried but not sintered).
[0085] Refer to the table below, which shows the polarization impedance values of the four full cells at various test temperatures and gas volumes. As the test temperature increases, the planned impedance of the four full cells decreases. At the same time, as the test gas volume increases, the polarization impedance of the full cell increases. The sintering temperature of 600 degrees Celsius corresponds to the full cell, and its polarization impedance is the highest. On the one hand, the high sintering temperature increases the porosity of the battery cathode catalyst, increases the connection between the electrolyte and the catalyst, is conducive to the diffusion and transfer of ions and electrons, and reduces the polarization impedance of the battery; on the other hand, high-temperature sintering causes the high expansion characteristics of the battery cathode catalyst and the electrolyte to appear, resulting in thermal stress mismatch at the interface, cracks appear on the interface, and the actual catalytic area of the cathode catalyst is reduced, increasing the resistance to electron and ion transfer, and increasing the battery impedance. This makes the experimental sample sintered at 600 degrees Celsius of great significance, because the sample is at the inflection point of this two-sided nature. At the same time, due to the significance of the inflection point of sintering at 600 degrees Celsius, we believe that it balances the advantages of both sides. That is, it has both the high porosity of the cathode catalyst brought by high sintering and the tighter connection between the electrode and the electrolyte (which is conducive to the stability of the battery during long-term testing), and the low stress between the electrolyte and the cathode electrode at low sintering temperature, which effectively increases the actual catalytic area of the cathode catalyst (improves the polarization performance of the battery) and has a positive effect on battery performance. In summary, we believe that the optimal sintering temperature for dispersed spot coating is 600 degrees Celsius, and it is believed that it has better polarization performance (compared with conventional methods) and better stability (compared with other sintering methods).
[0086]
[0087] Reference Figure 1 The electrochemical performance tests (IV and IP curves) of the samples sintered at 600 degrees Celsius in Example 1 were carried out at different temperatures. The results showed that the dispersed coating in Example 1 helped to alleviate the interface damage caused by thermal expansion, increased the actual catalytic area, reduced the cathode polarization impedance, and increased the battery power density to 1833.30 milliwatts per square centimeter (at 850 degrees Celsius). Figure 1 In the IV and IP curves, the order from the lower curve to the upper curve are the test conditions of 700 degrees Celsius, 750 degrees Celsius, 800 degrees Celsius and 850 degrees Celsius, and the hydrogen condition is 30 ml per minute.
[0088] For Example 1, we also used DRT technology and Nyquist diagram ( Figure 2 , Figure 3) analyzed the behavior of the interface between the electrode and the electrolyte layer. The results showed that the dispersed spot coating method can effectively reduce the negative effect of thermal expansion on battery performance, especially in the temperature range of 700 degrees Celsius to 850 degrees Celsius, the polarization impedance of the battery decreases with increasing temperature, showing good thermal stability. Through a series of full battery tests, it was proved that the dispersed spot coating La 0.95 Ag 0.05 CoO 3 ||YSZ||The maximum power density of the NIO-YSZ full battery at different test temperatures far exceeds that of conventional cathode materials, and under specific conditions (such as sintering at 600 degrees Celsius and working at 700 degrees Celsius), the polarization resistance value drops to 0.587 ohms per square centimeter (700 degrees Celsius) and 0.246 ohms per square centimeter (850 degrees Celsius), reaching ideal performance indicators. Figure 4 In the 100-hour polarization resistance test at 700°C, the polarization impedance fluctuation of the cathode battery using the dispersed spot coating method during thermal cycling was very small, indicating that this method helps to improve the stability and durability of the battery during multiple thermal cycles.
[0089] Embodiment 2:
[0090] In Example 2, except that the cathode material is La 0.9 Ag 0.1 CoO 3 Except for this, the other components and process are consistent with those in Example 1. Figure 5 The EIS spectrum measurements performed at different test temperatures are given in the figure, and the curve in the figure shows typical two semicircular arcs. As the temperature increases, the entire spectrum moves to a low value on the real axis and the imaginary axis, and the transition can be attributed to the enhancement of the ionic conductivity and surface reaction of the entire fuel cell. In the Nyquist diagram of impedance, the high-frequency intercept (left intersection) of the impedance curve with the real axis is the ohmic resistance, and the low-frequency intercept (right intersection) with the real axis is the total resistance; the difference between the total resistance and the ohmic resistance is the polarization resistance. In the embodiment, the polarization resistance (ohms per square centimeter) and the ohmic resistance (ohms per square centimeter) are 0.146 and 0.18 (850 degrees Celsius), 0.251 and 0.283 (800 degrees Celsius), 0.379 and 0.408 (750 degrees Celsius), 0.587 and 0.632 (700 degrees Celsius), respectively. In Example 2, the polarization resistance (ohm per square centimeter) and the ohmic resistance (ohm per square centimeter) are 0.155 and 0.190 (850 degrees Celsius), 0.241 and 0.290 (800 degrees Celsius), 0.415 and 0.450 (750 degrees Celsius), and 0.653 and 0.700 (700 degrees Celsius), respectively. Figure 5In the Nyquist diagram of impedance, the order from the upper curve to the lower curve is the test conditions of 700 degrees Celsius, 750 degrees Celsius, 800 degrees Celsius and 850 degrees Celsius respectively; Figure (a) hydrogen condition is 30 ml per minute, Figure (b) hydrogen condition is 50 ml per minute. Under different test temperatures (700 degrees Celsius to 850 degrees Celsius) and hydrogen flow rates (30 to 50 ml per minute), the complex relationship between the battery's ohmic polarization, activation polarization and concentration polarization and operating conditions is revealed through the analysis of electrochemical impedance spectroscopy (EIS) and polarization curves. For example, at 750 degrees Celsius, with the hydrogen flow rate of 30 to 50 ml per minute, the polarization impedance shows an abnormal increase in the high-frequency region. This is because although the increase in hydrogen flow can theoretically reduce ohmic polarization, it actually increases the cathode concentration polarization in actual operation, especially when the thermal expansion mismatch between the cathode material and the electrolyte layer is aggravated.
[0091] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made by using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A solid oxide fuel cell cathode, It is characterized in that include: The cathode middle layer is made of rare earth oxide doped material; The cathode body comprises a plurality of cathode points discretely distributed and combined on the cathode intermediate layer, wherein the cathode points comprise a plurality of cathode point layers combined in the thickness direction, wherein the cathode body is made of a perovskite type material.
2. The solid oxide fuel cell cathode according to claim 1, It is characterized in that The density of the plurality of cathode point layers on the cathode point increases gradually by 5% to 20% in the direction away from the cathode middle layer.
3. The solid oxide fuel cell cathode according to claim 2, It is characterized in that The cathode intermediate layer includes a plurality of sub-intermediate layers coupled in a thickness direction.
4. The solid oxide fuel cell cathode according to claim 3, It is characterized in that The cathode intermediate layer comprises at least three sub-intermediate layers; the density of the sub-intermediate layers at the outer layer in the thickness direction increases gradually from 5% to 20% toward the density of the sub-intermediate layers at the middle part in the thickness direction.
5. The solid oxide fuel cell cathode according to any one of claims 1 to 4, It is characterized in that The material of the cathode body is Co-based perovskite.
6. The solid oxide fuel cell cathode according to claim 5, It is characterized in that The material of the cathode body is La x Ag (1-x) CoO 3 .
7. The solid oxide fuel cell cathode according to any one of claims 1 to 4, It is characterized in that The material of the cathode intermediate layer is gadolinium-doped ceria.
8. A production process, It is characterized in that the steps include: S1. Complete cathode intermediate layer slurry configuration; S2, taking cathode intermediate layer slurry to complete the lamination printing of sub-intermediate layers to form a substrate, wherein each sub-intermediate layer is dried after printing, and the sub-intermediate layers together constitute an intermediate layer; S3, completing cathode body slurry configuration; S4, taking the cathode body slurry and using a porous film layer to print the stacked layers of sub-cathode dots on the substrate to form a cathode prefabricated sheet, wherein each batch of sub-cathode dots is dried after printing, and the sub-cathode dots at the same position together constitute an independent cathode dot; S5. Complete sintering of the cathode prefabricated sheet.
9. The manufacturing process according to claim 8, It is characterized in that The steps of S3 include: Disposing a plurality of cathode point layer slurries with concentration gradient differences; The steps of S4 include: Take multiple cathode dot layer slurries and use a porous membrane layer to print the stacked sub-cathode dot layers on a substrate to form a cathode prefabricated sheet, wherein each batch of sub-cathode dot layers are dried after printing, and the sub-cathode dot layers at the same position together constitute an independent cathode point, and the density of multiple cathode dot layers on the cathode point increases by 5% to 20% in the direction away from the cathode middle layer.
10. The manufacturing process according to claim 8, It is characterized in that The steps of S1 include: Disposing a plurality of sub-middle layer slurries with different concentration gradients; The steps of S2 include: Take multiple sub-intermediate layer slurries to complete the stacking printing of sub-intermediate layers to form a base sheet, wherein each sub-intermediate layer is dried after printing, and the sub-intermediate layers together constitute an intermediate layer, and the density of the sub-intermediate layer in the outer layer in the thickness direction increases gradually from 5% to 20% toward the density of the sub-intermediate layer in the middle in the thickness direction.
